Exploring the Power and Regulation of Platform Enterprises - Li, Xintong; Li, Yidi (International Journal of Social Sciences and Public Administration, 2024)
In the age of information civilization, digital platform enterprises are developing vigorously. At the same time, power is generated based on the algorithm.These information giants, based on their power to control data and privacy, exercise the power of punishment, and participate in the collection, distribution and maintenance of public resources and public interests. The nature of this kind of behavior is highly similar to that carried out by the administrative subject. At present, the regulation of platform enterprises is not perfect, which is mainly restricted through data method.But it is difficult to cover their participation in public services. The defining feature of administrative disputes lies in the public nature of the actions involved, rather than the identity of the actors. As private entities and their behaviors increasingly assume a public dimension in the information age, a shift in regulatory approaches is warranted. In the future, the scope of administrative litigation could be expanded to include platform enterprises that hold significant power, thereby providing a framework for regulation.